Limited Immunogenicity of HIV CD8⁺ T-Cell Epitopes in Acute Clade C Virus Infection - Radebe, Mopo; Nair, Kriebashnie; Chonco, Fundisiwe; Bishop, Karen; Wright, Jaclyn K.; van der Stok, Mary; Basse, Ingrid V.; Mncube, Zenele; Altfeld, Marcus; Walker, Bruce D.; Ndung'u, Thumbi (The Journal of infectious diseases, 2011)
Background. Human immunodeficiency virus type 1 (HlV-1)-specific CD8⁺ responses contribute to the decline in acute peak viremia following infection. However, data on the relative immunogenicity of CD8⁺ T-cell epitopes during and after acute viremia are lacking. Methods. We characterized CD8⁺ T-cell responses in 20 acutely infected, antiretro viral-naive individuals with HIV-1 subtype C infection using the interferon-γ enzyme-linked immunosorbent spot assay. Eleven of these had not fully seroconverted at the time of analysis. Viruses from plasma were sequenced within defined cytotoxic T-lymphocyte (CTL) cell epitopes for selected subjects. Results. At approximately 28 days after estimated initial infection, CD8⁺ T-cell responses were directed against an average of 3 of the 410 pep tides tested (range, 0-6); 2 individuals had no detectable responses at this time. At 18 weeks, the average number of peptides targeted had increased to 5 (range 0-11). Of the 56 optimal Gag CTL epitopes sequenced, 31 were wild-type in the infecting viruses, but only 11 of 31 elicited measurable CD8⁺ T-cell responses. Conclusions. These data demonstrate that the majority of CD8⁺ responses are not elicited during acute HIV infection despite the presence of the cognate epitope in the infecting strain. There is a need to define factors that influence lack of induction of effective immune responses and the parameters that dictate immunodominance in acute infection.